2014
DOI: 10.1111/clr.12370
|View full text |Cite
|
Sign up to set email alerts
|

Two‐piece zirconia implants supporting all‐ceramic crowns: A prospective clinical study

Abstract: ObjectivesThe aim of this prospective clinical study is to evaluate the safety and efficacy of a new all-ceramic implant system to replace missing teeth in partially edentulous patients.Material and methodsThirty-two partially edentulous, systemically healthy patients were treated with 49 two-piece zirconia implants (ZERAMEX® T Implant System). Zirconia abutments were connected with adhesive resin cement. Single-unit full-ceramic crowns were cemented. The cases have been followed for 588±174 days after loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
121
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(141 citation statements)
references
References 26 publications
(26 reference statements)
9
121
1
4
Order By: Relevance
“…Cionca et al reported that cumulative survival rate was 87% after 1 year loading. 17 The stated failure reason was aseptic loosening, and no implants were lost after first year and the results of the other cases were good. In this clinical report, single-tooth replacement with one-piece and twopiece zirconia implant treatment in the anterior region were evaluated.…”
Section: Figurementioning
confidence: 86%
See 1 more Smart Citation
“…Cionca et al reported that cumulative survival rate was 87% after 1 year loading. 17 The stated failure reason was aseptic loosening, and no implants were lost after first year and the results of the other cases were good. In this clinical report, single-tooth replacement with one-piece and twopiece zirconia implant treatment in the anterior region were evaluated.…”
Section: Figurementioning
confidence: 86%
“…[11][12][13][14][15][16] Firstly one-piece implants were introduced. 17 However there are ambitions to fabricate two-piece zirconia comparable to two-piece titanium implants. 13 The purpose of this article is to give information about the dental zirconia implants and present 4 cases treated with one-piece and two-piece zirconia implants located in the anterior maxillary region.…”
Section: Reconstruction Of Single Tooth Loss Withmentioning
confidence: 99%
“…The two-part design is also a requirement for a flexible restoration with a lot of freedom. The stability of zirconium oxide is similar to titanium: strength tests (ISO 14801) show the high break resistance and durability [29].…”
Section: Zeramex® (Pubmed -4 Publications : 2015-2016)mentioning
confidence: 99%
“…Two piece can be corrected [28] Adherence to Plaque Does not adhere to plaque [32] Adheres to Plaque [ 32] Fracture Tendency It may fracture [20] No or less prone to fractures [28] Fracture Tendency It may fracture [20] No or less prone to fractures [28] Margin At gingival level [32] At bone level [32] Maintenance Easier to maintain [32] Harder to maintain [32] Corrosion Resistant to Corrosion [26] Metal corrosion can occur [26] Allergic Reactions No allergic reaction [32] May have allergic reaction [20] Osseo-integration Less [26] More [26] Surface Roughness Smooth [20] Rough(more bone apposition) [20] Discussion…”
Section: Only One Piecementioning
confidence: 99%